A Preliminary Study of Internal Corrosion in Condensate Pipelines at Geothermal Power Plants - Royani, Ahmad; Prifiharni, Siska; Priyotomo, Gadang; Triwardono, Joko; Sundjono (International Journal of Integrated Engineering, 2021)
In this study, we presented observations and analyze related to internal corrosion in condensate pipes in geothermal power plants. A damaged pipe of condensate pipeline taken from a power plant was investigated to determine the root cause of failure. The observation and failure analysis was carried out by visual and dimensional examination, chemical composition testing, macroscopic, and microscopic examination, Scanning Electron Microscope (SEM) examination with Energy Dispersed Spectrometer (EDS). The deposit in the pipe was analyzed by X-Ray Diffraction (XRD). The quality of the condensate fluid and their tendencies were determined by Langelier Saturation Index (LSI). Also, the corrosion rate of the pipe was simulated by condensate fluid by using a corrosion measurement system (Tafel polarization). The internal corrosion was found in the condensate line is strongly suspected to occur due to erosion-corrosion. Erosion corrosion is caused by insoluble and hard particles in the condensate fluid. The results of XRD found the presence of calcium-silicate compounds in the sediment that is suspected to be the cause of erosion particles. The reduction of the thickness of the bottom pipe wall and occurs in longitudinal directions the alleged damage to the pipe due to sediment corrosion. The presence of hard compounds and differential oxygen can accelerate the process of corrosion so that the corrosion rate in condensate pipelines was a category in the severe category based on NACE SP0775 standards.